(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In our country demand of wood as building material is rapidly growing .Now situation has led to use environment friendly construction structurally safe another material. It alone represent more than 25-35 of total construction cost of house .By using asbestos cement roofing sheet causes health problem.there is need to replace asbestos, wood by eco-friendly material. Sisal fiber is locally available eco-friendly material having low density high strength durability reasonable cost. Sisal is biodegradable organic fiber material.By using epoxy chemical in fabrication of sisal fibers composite we get hardness in particular panel. This paper analyzes the sisal fiber is construction material which is used for low cost housing purpose also presents a summary of recent development of sisal fiber its composite